The Analysis of the Cutting Forces and Surface Layer Stereometry in the Grinding Process of Abrasion-Resisting Materials - Wójcik, Ryszard; Grdulska, Anna; Rosik, Radosław; Wejman, Przemysław (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
The article presents the investigation of the grinding process of flat samples made of materials that meet requirements of the lowest abrasibility, which belong to difficult to machine materials. Research enclosed measurement of cutting forces and surface layer stereometry during grinding without using cutting fluid. The tests were carried out with the aid of new generation grinding wheel, Quantum.
Keywords: Quantum; wear; XAR 400; Brinar 400; Dillidur 500V; grinding; szlifowanie; stereometria warstwy powierzchniowej; materiały odporne na ścieranie; proces szlifowania